Analiza powiązań strukturalnych Dzielnicy Nowe Miasto w Zielonej Górze = Analysis of structural structures of the District New City in Zielona Góra - Andrzejewska, Ewelina; Bazan-Krzywoszańska, Anna; Skiba, Marta; Stępkowska, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a structural analysis of determinants in terms of the number of inhabitants and their access to basic services. The analysis covered the part of the city (District Nowe Miasto) included on January 1, 2015 into the administrative area of the commune of Zielona Góra and the potential for the development of urban efficiency. In the article, mutual relations in the urban system are described as flows related to the allocation of people, assuming that the structure of the system includes the spatial distribution of elements, the manner of their constant relations and the time-varying interactions between them.
Keywords: planowanie przestrzenne; miejski zespół usługowy; analiza dostępności usług; spatial planning; urban service system; analysis of service availabil